eCulture : cultural content in the digital age - Ronchi, Alfredo M. (Springer, 2009)
Do virtual museums really provide added value to end-users, or do they just contribute to the abundance of images?Does the World Wide Web save endangered cultural heritage, or does it foster a society with less variety?How can information technology help to preserve the diversity of cultures in our fast-changing world?.